Sustainability in wine tourism: a bibliometric and content review - Fontes, Filipa (2024)
The wine sector increasingly recognizes the importance of adopting sustainable practices. In tourism, sustainability works as a valuable and appropriate tool to attract tourists, who are increasingly selecting companies that have sustain- able performance. This paper aims to identify and analyze the existing literature related to the topic of sustainability in wine tourism. Based on a literature review, this study provides an analysis of the most important topics in the research related to sustainability in wine tourism. This analysis is divided into two phases, a qualitative analysis with a literature review, and a bibliometric analysis through VosViewer. The results show that sustainability in wine tourism has been an area of growing interest, with a greater number of publications in recent years. The most recent research topics are related to the strategic approach, competitiveness, covid-19, spatial-temporal analysis, and sustainable practices.